Finished ware entering tempering oven at glass factory (Underwood & Underwood)
View of a worker transferring a finished ware to the tempering over at a Glass Works factory in New Jersey. This photograph is one of a set of five stereographs detailing the production of blown-glass bottles.
Keywords: Employees; Glass blowing and working; Manufacturing industries; Glass manufacture